Flame-retardant polytetrafluoroethylene composite and method of making

CN121718111BActive Publication Date: 2026-09-11SHANGHAI XINWANG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610106774.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-27
Publication Date
2026-09-11
Estimated Expiration
2046-01-27

AI Technical Summary

Technical Problem

[0004]本发明解决的技术问题是:解决了聚四氟乙烯材料强度和耐磨损性能不佳的问题

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of new materials, and discloses a flame-retardant polytetrafluoroethylene composite material and a preparation method.The flame-retardant polytetrafluoroethylene composite material is prepared by ball-milling, mold pressing and sintering of polytetrafluoroethylene resin, polyimide resin and fluorine-containing imide phenolic resin in a proportion of (65-90) g:(10-35) g:(2-5) g, and the flame-retardant polytetrafluoroethylene composite material is obtained.The fluorine-containing imide phenolic resin improves the compatibility between the polytetrafluoroethylene and the polyimide, the polyimide is uniformly dispersed in the polytetrafluoroethylene matrix, the tensile strength and the wear resistance of the composite material are improved, and the high-temperature resistance and the flame retardance are excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new materials technology, specifically to a flame-retardant polytetrafluoroethylene composite material and its preparation method. Background Technology

[0002] Polytetrafluoroethylene (PTFE) has good heat resistance, excellent water and corrosion resistance, and high flame retardancy. It is widely used in high-performance coatings, seals, machinery manufacturing, aerospace and other fields. Although PTFE has a very low coefficient of friction, it has a high wear rate and poor wear resistance when rubbing against metal materials, which limits the practical application of PTFE.

[0003] Phenolic resins possess excellent heat resistance, superior bonding properties, and some flame retardant characteristics, making them important in wear-resistant materials such as sandpaper and brake discs. Polyimide is one of the best-performing polymer materials, exhibiting high mechanical strength, high-temperature resistance, and wear resistance. Blending polyimide with polytetrafluoroethylene (PTFE) produces composite materials with even better wear resistance. However, polyimide and PTFE have poor compatibility; directly mixing them can negatively impact the strength and other properties of the composite material. Summary of the Invention

[0004] The technical problem solved by this invention is to address the issue of poor strength and wear resistance of polytetrafluoroethylene (PTFE) materials.

[0005] The technical solution of this invention is: a method for preparing flame-retardant polytetrafluoroethylene composite material: (1) Add glacial acetic acid, tetrafluorophthalic anhydride and 4-hydroxyaniline to the reaction vessel, heat to the reaction temperature, stir and reflux the reaction, cool the solution in an ice-water bath, filter and wash the filter cake with water and ethanol, dry to obtain N-(4-hydroxyphenyl)tetrafluorophthalimide.

[0006] (2) Add phenol and N-(4-hydroxyphenyl)tetrafluorophthalimide to the reaction vessel, stir, add an aqueous solution of formaldehyde, heat to the reaction temperature, add concentrated hydrochloric acid dropwise, stir, condense and reflux the reaction, remove water and other low-boiling substances by vacuum distillation, and obtain fluorinated imide phenolic resin.

[0007] (3) Add polytetrafluoroethylene resin, polyimide resin, fluorinated imide phenolic resin and N,N-dimethylformamide to a ball mill, mix them by ball milling, dry them and then mold the mixture in a molding press, and then place it in a sintering furnace to sinter to obtain flame-retardant polytetrafluoroethylene composite material.

[0008] Furthermore, in (1), the ratio of tetrafluorophthalic anhydride to 4-hydroxyaniline is 1 mol: (1-1.3) mol.

[0009] Furthermore, in (1), the reaction temperature is 110-120℃ and the reaction time is 4-6h.

[0010] Furthermore, in (2), the ratio of phenol, N-(4-hydroxyphenyl)tetrafluorophthalimide, and formaldehyde is (0.7-0.9) mol: (0.1-0.3) mol: (1.2-1.4) mol.

[0011] Furthermore, in (2), the reaction temperature is 90-100℃ and the reaction time is 3-4h.

[0012] Furthermore, in (3), the ball milling speed is 300-600 r / min and the ball milling time is 2-4 h.

[0013] Furthermore, in (3), the pressure during compression molding is 30-50 MPa and the time is 7-10 min.

[0014] Furthermore, in (3), the sintering process involves raising the temperature from room temperature to 380-385℃ at a rate of 2-5℃ and holding it at that temperature for 3-4 hours.

[0015] Furthermore, in (3), the ratio of polytetrafluoroethylene resin, polyimide resin, and fluorinated imide phenolic resin is (65-90) g: (10-35) g: (2-5) g.

[0016] The beneficial technical effects of this invention are as follows: N-(4-hydroxyphenyl)tetrafluorophthalimide is used as a high-performance phenol monomer and undergoes a polycondensation reaction with phenol and formaldehyde to obtain a fluorinated imide phenolic resin. Then, it is ball-milled and blended with polytetrafluoroethylene and polyimide, and then molded and sintered to obtain a flame-retardant polytetrafluoroethylene composite material. This fluorinated imide phenolic resin contains a large amount of fluorine and a phenylphthalimide structure similar to that of polyimide, which allows the fluorinated imide phenolic resin to act as a compatibilizer, improving the compatibility between polytetrafluoroethylene and polyimide. The polyimide is uniformly dispersed in the polytetrafluoroethylene body, thus improving the mechanical properties of the composite material.

[0017] The phenolic resin in this invention possesses excellent bonding properties and can act as a binder to improve the interfacial bonding strength between polyimide and polytetrafluoroethylene (PTFE), resulting in higher internal density of the composite material, higher tensile strength, significantly reduced volumetric wear rate, and improved wear resistance. Simultaneously, it maintains a high initial thermal decomposition temperature and exhibits excellent high-temperature resistance. PTFE, phenolic resin, and polyimide themselves possess excellent flame retardancy, and the prepared composite material exhibits excellent flame-retardant properties, making it suitable for applications such as high-strength, wear-resistant, and flame-retardant aerospace composite materials. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. To achieve the above objectives, the invention adopts the following technical solutions.

[0019] Example 1 (1) 60 mL of glacial acetic acid, 30 mmol of tetrafluorophthalic anhydride, and 39 mmol of 4-hydroxyaniline were added to a reaction vessel. The mixture was heated to 120 °C, stirred, and refluxed for 4 h. The solution was cooled in an ice-water bath, filtered, and the filter cake was washed with water and ethanol and dried to obtain N-(4-hydroxyphenyl)tetrafluorophthalimide. The reaction formula is: .

[0020] (2) Add 83 mmol of phenol and 17 mmol of N-(4-hydroxyphenyl)tetrafluorophthalimide to the reaction vessel, stir, add 12 mL of aqueous solution containing 120 mmol of formaldehyde, heat to 100 °C, add 0.06 mL of concentrated hydrochloric acid (mass fraction 37%), stir, reflux for 3 h, remove water and other low-boiling substances by vacuum distillation, and obtain fluorinated imide phenolic resin.

[0021] (3) Add 900g of polytetrafluoroethylene resin, 100g of polyimide resin, 20g of fluorinated imide phenolic resin and 300mL of N,N-dimethylformamide to a ball mill and mix for 2h at a speed of 400r / min. After drying, mold the mixture in a molding press at 40MPa for 7min and then place it in a sintering furnace for sintering. The temperature is increased from room temperature to 380℃ at a rate of 2℃ and sintered for 3h to obtain flame-retardant polytetrafluoroethylene composite material.

[0022] Example 2 (1) Add 50 mL of glacial acetic acid, 30 mmol of tetrafluorophthalic anhydride and 30 mmol of 4-hydroxyaniline to the reaction vessel, heat to 110 °C, stir and reflux for 6 h, cool the solution in an ice-water bath, filter, wash the filter cake with water and ethanol, and dry to obtain N-(4-hydroxyphenyl)tetrafluorophthalimide.

[0023] (2) Add 90 mmol of phenol and 10 mmol of N-(4-hydroxyphenyl)tetrafluorophthalimide to the reaction vessel, stir, add 14 mL of aqueous solution containing 130 mmol of formaldehyde, heat to 90 °C, add 0.08 mL of concentrated hydrochloric acid (mass fraction 37%) dropwise, stir, reflux and condense for 4 h, remove water and other low-boiling substances by vacuum distillation, and obtain fluorinated imide phenolic resin.

[0024] (3) Add 850g of polytetrafluoroethylene resin, 150g of polyimide resin, 28g of fluorinated imide phenolic resin and 300mL of N,N-dimethylformamide to a ball mill and mix for 3h at a speed of 600r / min. After drying, mold the mixture in a molding press at 30MPa for 10min and then place it in a sintering furnace for sintering. The temperature is increased from room temperature to 380℃ at a rate of 5℃ and sintered for 4h to obtain flame-retardant polytetrafluoroethylene composite material.

[0025] Example 3 (1) N-(4-hydroxyphenyl)tetrafluorophthalimide was prepared according to the method of Example 1.

[0026] (2) Add 70 mmol of phenol and 30 mmol of N-(4-hydroxyphenyl)tetrafluorophthalimide to the reaction vessel, stir, add 12 mL of aqueous solution containing 120 mmol of formaldehyde, heat to 90 °C, add 0.08 mL of concentrated hydrochloric acid (mass fraction 37%) dropwise, stir, reflux and condense for 4 h, remove water and other low-boiling substances by vacuum distillation, and obtain fluorinated imide phenolic resin.

[0027] (3) 750g of polytetrafluoroethylene resin, 250g of polyimide resin, 40g of fluorinated imide phenolic resin and 200mL of N,N-dimethylformamide were added to a ball mill and mixed for 4h at a speed of 300r / min. After drying, the mixture was molded in a molding press at 50MPa for 7min and then placed in a sintering furnace for sintering. The temperature was increased from room temperature to 385℃ at a heating rate of 5℃ and sintered for 3h to obtain flame-retardant polytetrafluoroethylene composite material.

[0028] Example 4 (1) N-(4-hydroxyphenyl)tetrafluorophthalimide was prepared according to the method of Example 1.

[0029] (2) Add 77 mmol phenol and 23 mmol N-(4-hydroxyphenyl)tetrafluorophthalimide to the reaction vessel, stir, add 15 mL of aqueous solution containing 140 mmol formaldehyde, heat to 90 °C, add 0.09 mL concentrated hydrochloric acid (mass fraction 37%) dropwise, stir, reflux and condense for 4 h, remove water and other low-boiling substances by vacuum distillation, and obtain fluorinated imide phenolic resin.

[0030] (3) Add 650g of polytetrafluoroethylene resin, 350g of polyimide resin, 50g of fluorinated imide phenolic resin and 200mL of N,N-dimethylformamide to a ball mill and mix for 2 hours at a speed of 500r / min. After drying, mold the mixture in a molding press at 40MPa for 8 minutes, and then place it in a sintering furnace for sintering. The temperature is increased from room temperature to 380℃ at a heating rate of 3℃, and the temperature is held for 4 hours to obtain flame-retardant polytetrafluoroethylene composite material.

[0031] Comparative Example 1 (1) 100 mmol phenol and 12 mL aqueous solution containing 120 mmol formaldehyde were added to the reaction vessel, heated to 100 °C, and 0.06 mL concentrated hydrochloric acid (mass fraction 37%) was added dropwise. The mixture was stirred, refluxed, and stirred for 3 h. Low-boiling substances such as water were removed by vacuum distillation to obtain phenolic resin.

[0032] (2) Add 900g of polytetrafluoroethylene resin, 100g of polyimide resin, 20g of phenolic resin and 300mL of N,N-dimethylformamide to a ball mill and mix for 2 hours at a speed of 400r / min. After drying, mold the mixture in a molding press at 40MPa for 7 minutes, and then place it in a sintering furnace for sintering. The temperature is increased from room temperature to 380℃ at a rate of 2℃, and the temperature is held for sintering for 3 hours to obtain flame-retardant polytetrafluoroethylene composite material.

[0033] Comparative Example 2 (1) 83 mmol phenol and 17 mmol 4-trifluoromethylphenol (CAS No. 402-45-9) were added to the reaction vessel. After stirring, 12 mL of aqueous solution containing 120 mmol formaldehyde was added. The mixture was heated to 100 °C and 0.06 mL of concentrated hydrochloric acid (mass fraction 37%) was added dropwise. The mixture was stirred and refluxed for 3 h. Water and other low-boiling substances were removed by vacuum distillation to obtain fluorinated phenolic resin.

[0034] (2) 900g of polytetrafluoroethylene resin, 100g of polyimide resin, 20g of fluorinated imide phenolic resin and 300mL of N,N-dimethylformamide were added to a ball mill and mixed for 2 hours at a speed of 400r / min. After drying, the mixture was molded in a molding press at 40MPa for 7 minutes and then placed in a sintering furnace for sintering. The temperature was increased from room temperature to 380℃ at a rate of 2℃ and sintered for 3 hours to obtain flame-retardant polytetrafluoroethylene composite material.

[0035] Comparative Example 3 (1) 60 mL of glacial acetic acid, 30 mmol of phthalic anhydride, and 39 mmol of 4-hydroxyaniline were added to a reaction vessel. The mixture was heated to 120 °C, stirred, and refluxed for 4 h. The solution was cooled in an ice-water bath, filtered, and the filter cake was washed with water and dried to obtain N-(4-hydroxyphenyl)phthalimide with the structural formula: .

[0036] (2) Add 83 mmol of phenol and 17 mmol of N-(4-hydroxyphenyl) phthalimide to the reaction vessel, stir, add 12 mL of aqueous solution containing 120 mmol of formaldehyde, heat to 100 °C, add 0.06 mL of concentrated hydrochloric acid (mass fraction 37%), stir, reflux for 3 h, remove water and other low-boiling substances by vacuum distillation, and obtain imide phenolic resin.

[0037] (3) Add 900g of polytetrafluoroethylene resin, 100g of polyimide resin, 20g of imide phenolic resin and 300mL of N,N-dimethylformamide to a ball mill and mix for 2 hours at a speed of 400r / min. After drying, mold the mixture in a molding press at 40MPa for 7 minutes, and then place it in a sintering furnace for sintering. The temperature is increased from room temperature to 380℃ at a rate of 2℃, and the temperature is held for sintering for 3 hours to obtain flame-retardant polytetrafluoroethylene composite material.

[0038] The wear resistance of the composite material was tested using a wear testing machine. The mating part was a GCr15 steel ring, the load was 200N, the rotation speed was 300r / min, and the time was 1h. The volume difference ΔV and the wear mark width L before and after wear were measured, and the volume wear rate W was calculated. W=ΔV / (P×L), where L is the sliding distance.

[0039] The tensile strength of the material shall be tested according to GB / T 1040.1-2025 standard.

[0040] The composite material was placed in a thermogravimetric analyzer and its thermogravimetric properties were analyzed in a nitrogen atmosphere. The heating rate was 5℃ / min and the temperature range was 20-800℃.

[0041] Table 1 Performance of Flame-Retardant Polytetrafluoroethylene Composite Materials Example 1 38.4 7.21 508.4 Example 2 46.3 5.58 528.6 Example 3 51.0 2.79 521.7 Example 4 54.6 3.15 510.1 Comparative Example 1 33.8 7.83 507.9 Comparative Example 2 34.2 7.78 502.5 Comparative Example 3 34.7 7.70 506.1 Comparative Example 1 involved blending and molding polyimide and polytetrafluoroethylene. Due to their poor compatibility, the composite material exhibited low tensile strength, high volumetric wear rate, and poor mechanical strength and wear resistance.

[0042] Examples 1-4 incorporated fluorinated imide phenolic resin, which contains a large amount of fluorine and a phenylphthalimide structure similar to polyimide. This allows the fluorinated imide phenolic resin to act as a compatibilizer, improving the compatibility between polytetrafluoroethylene (PTFE) and polyimide. The polyimide is uniformly dispersed in the PTFE matrix, improving the mechanical properties of the composite material. Furthermore, the phenolic resin itself has good adhesive properties and can act as a binder to improve the interfacial bonding strength between polyimide and PTFE, resulting in higher internal density of the composite material, higher tensile strength, significantly reduced volumetric wear rate, and improved wear resistance. The addition of an appropriate amount of fluorinated imide phenolic resin also gives the composite material a high initial thermal decomposition temperature (5% mass loss) and excellent high-temperature resistance.

[0043] The phenolic resin in Comparative Example 1 does not contain fluorine or phenyl phthalimide structure, the fluorinated imide phenolic resin in Comparative Example 2 does not contain phenyl phthalimide structure, and the imide phenolic resin in Comparative Example 3 does not contain fluorine. All three are difficult to improve the compatibility between polytetrafluoroethylene and polyimide. The composite materials of the three have low tensile strength, high volumetric wear rate, and poor wear resistance.

[0044] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art will recognize that other variations or modifications can be made based on the above description.

Claims

1. A method for preparing a flame-retardant polytetrafluoroethylene composite material, characterized in that, The flame-retardant polytetrafluoroethylene composite material comprises polytetrafluoroethylene resin, polyimide resin, and fluorinated imide phenolic resin in a ratio of (65-90)g:(10-35)g:(2-5)g. The preparation method is as follows: polytetrafluoroethylene resin, polyimide resin, fluorinated imide phenolic resin, and N,N-dimethylformamide are added to a ball mill, ball milled and mixed, dried, and then the mixture is molded in a molding press and then placed in a sintering furnace for sintering to obtain flame-retardant polytetrafluoroethylene composite material. The preparation method of the fluorinated imide phenolic resin includes: (1) Add glacial acetic acid, tetrafluorophthalic anhydride and 4-hydroxyaniline to the reaction vessel, heat to the reaction temperature, stir the reaction, cool the solution in an ice-water bath, filter, wash the filter cake, and dry to obtain N-(4-hydroxyphenyl)tetrafluorophthalimide; (2) Add phenol and N-(4-hydroxyphenyl)tetrafluorophthalimide to the reaction vessel, stir, add an aqueous solution of formaldehyde, heat to the reaction temperature, add concentrated hydrochloric acid dropwise, stir the reaction, and distill under reduced pressure to obtain fluorinated imide phenolic resin. The ratio of tetrafluorophthalic anhydride and 4-hydroxyaniline in (1) is 1 mol: (1-1.3) mol; The ratio of phenol, N-(4-hydroxyphenyl)tetrafluorophthalimide, and formaldehyde in (2) is (0.7-0.9) mol: (0.1-0.3) mol: (1.2-1.4) mol.

2. The method for preparing the flame-retardant polytetrafluoroethylene composite material according to claim 1, characterized in that, The ball milling speed is 300-600 r / min, and the ball milling time is 2-4 h.

3. The method for preparing the flame-retardant polytetrafluoroethylene composite material according to claim 1, characterized in that, The pressure during the compression molding process is 30-50 MPa, and the time is 7-10 min.

4. The method for preparing the flame-retardant polytetrafluoroethylene composite material according to claim 1, characterized in that, The sintering process involves raising the temperature from room temperature to 380-385°C at a rate of 2-5°C and holding it at that temperature for 3-4 hours.

5. The method for preparing the flame-retardant polytetrafluoroethylene composite material according to claim 1, characterized in that, The reaction temperature in (1) is 110-120℃ and the reaction time is 4-6h.

6. The method for preparing the flame-retardant polytetrafluoroethylene composite material according to claim 1, characterized in that, The reaction temperature in (2) is 90-100℃ and the reaction time is 3-4h.

7. A flame-retardant polytetrafluoroethylene composite material obtained by the preparation method according to any one of claims 1-6.

Citation Information

Patent Citations

  • Polytetrafluoroethylene composite material and preparation method thereof

    CN102719044A

  • Wear-resistant anti-static polytetrafluoroethylene composite material and preparation process thereof

    CN118126478A